Commercial Aspects of Self-Help Group Banking in India: A Study of Bank Transaction Costs - Harishkumar R. Dave; Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2002)
There are two outstanding aspects to Nabard's Linking Banks and Self-Help Groups: with an outreach to 500,000 SHGs and a population of 40m rural poor, it is the largest non-directed microsavings & microcredit program in the developing world; and its bank lending rates – fluctuating at market rates around 7% in real terms – are among the lowest. Is it a commercial proposition for the 17,000 participating bank branches, and perhaps for another 20,000 who might join the program to reach a population of 100m by 2008? We are presenting a methodology for the study of financial products, applied to seven units of three banks in October 2002. The results are indicative only. We applied average cost analysis, attributing all costs duly to each product; and marginal cost analysis, in response to the advice of bank managers to ignore personnel costs of SHG banking because of existing idle capacities. Main performance indicators are non-performing loans, return on average assets, and operational self-sufficiency. Non-performing loans to SHGs were 0%, testifying to the effectiveness of group lending to the very poor. In contrast, consolidated NPL ratios ranged from 2.6% to 18%; and of Cash Credit (CC) and Agricultural Term Loans (ATL) up to 55% and 62%, respectively. Returns on average assets of SHG Banking ranged from 1.4% to 7.5% by average and 4.6% to 11.8% by marginal cost analysis, compared to –1.7% to 2.3% consolidated. The operational self-sufficiency of SHG banking ranged from 110% to 165% by average and 142% to 286% by marginal cost analysis, compared to 86% to 145% consolidated. In contrast, ROA of Cash Credit varied from –10.2% to –0.5% and of ATL from –6.3% to 0.2%; OSS ratios from 54% to 102%. SHG Banking was found to be a robust financial product, performing well in healthy and distressed financial institutions. Self-reliance of SHGs based on internal savings and retained earnings was found to be rapidly growing, exceeding in older groups the volume of bank refinance by an increasing margin. In addition SHGs deposit substantial amounts of savings voluntarily in banks as a reserve for bad debts. In addition to direct effects on bank profits, SHG Banking has indirect commercial effects on banks in terms of improved overall vibrancy in banking activities. Indirect benefits at village level include the spreading of thrift and financial self-reliance and of a credit culture among villagers, micro-entrepreneurial experience, growth of assets and incomes, the spreading of financial management skills, and the decline of private money lending. Intangible social benefits are reportedly many: self-confidence and empowerment of women in civic affairs and local politics, improved school enrolment and women's literacy, better family planning and health, improved sanitation, reduction of drinking and smoking among men, and a decline in adherence to local extremism. The future sustainability of SHG Banking hinges on five factors: (a) A sound self-supporting institutional framework is in place. (b) Despite exceptionally low interest rates, linkage banking was found to be viable and profit-making for all financial institutions and SHGs; however, many rural banks require restructuring. (c) SHGs have substantially increased their level of self-reliance and deposited reserves, while banks are constrained by high statutory liquidity requirements. (d) Given the low inflation rate, preservation of the value of resources is no major issue, except in distressed banks. (e) With continually increasing internal funds, effective supervision of SHGs through a delegated system, together with the enforcement of prudential norms in banks and cooperatives, emerges as a major challenge to the long-term sustainability of SHG banking and rural finance in India. Among the topics for further study are: pricing of financial products in a random sample of rural financial institutions; extending SHG Banking to the middle poor; options of delegated supervision for SHGs and cooperatives; collateral for larger loans within SHGs; loan protection through life insurance; and options for individual performance incentives in banks and cooperatives.
Keywords: 330; Informeller Finanzsektor; Ländlicher Finanzmarkt; Selbsthilfe; Transaktionskosten; Indien